2015
DOI: 10.17988/0198-7429-40.3.171
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Enablers and Barriers Related to Sustainability of School-Wide Positive Behavioral Interventions and Supports

Abstract: The purpose of this study was to identify the most important perceived enablers and barriers regarding sustainability of school-wide positive behavioral interventions and supports. School personnel representing 860 schools implementing or preparing to implement school-wide positive behavioral interventions and supports completed an open-ended survey of factors regarding its sustainability. Qualitative analyses were used to assess perceptions of the most important factors related to sustainability. Thematic ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(73 citation statements)
references
References 35 publications
3
66
0
Order By: Relevance
“…This is consistent with CHILDHOOD OBESITY August 2020 S-49 other studies that have shown that schools have little time and few resources to implement school health programs. 61…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with CHILDHOOD OBESITY August 2020 S-49 other studies that have shown that schools have little time and few resources to implement school health programs. 61…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative analyses revealed that limited resources (including time and funding) were identified as the most significant barriers to sustaining SWPBIS; other frequently endorsed barriers included high rates of staff turnover, low fidelity of implementation, and insufficient staff buy-in. Pinkelman et al (2015) aimed to replicate and expand the results of McIntosh et al, using a larger and more diverse sample. Also based on qualitative analyses, the most frequently reported barriers were limited staff buy-in, followed by insufficient resources, both temporal (i.e., time to do SWPBIS activities) and monetary (i.e., funding).…”
Section: Barriers To Sustainability Of School-wide Positive Behavioramentioning
confidence: 98%
“…Participants noted more hindering than helping CIs in this category. This pattern may indicate some benefits of a supportive principal, but even stronger drawbacks of an unsupportive principal (Bambara et al, 2009;Pinkelman, McIntosh, Rasplica, Berg, & Strickland-Cohen, 2014). These findings may explain seemingly contradictory findings that school personnel perceive school administrators as the most important factor in promoting sustainability , whereas empirical studies from the same sample indicate administrator support as less influential than effective teaming and use of data for decision making (McIntosh et al, 2013).…”
Section: Unique Contributions or Elaborationsmentioning
confidence: 99%